Modus Kecurangan & Program Anti Kecurangan di Pelabuhan (Studi Kasus Pelabuhan di Jakarta) - Safuan Safuan; Budiandru Budiandru (Owner : Riset dan Jurnal Akuntansi, 2019)
The purpose of this study was to determine the anti-fraud and fraud in the port sector. The research method used in this research is a qualitative approach, with the case study. The results of this study found that fraud has been done by employees (employee fraud), management (management fraud), supplier (vendor fraud) and customer (customer fraud) and anti-fraud program, PT Pelindo II has launched IPC Bersih program as a form of implementation of Whistleblowing System.